Digitalisasi Buku Kas Aplikasi E-Nota Pada Pelaku UMKM Kelurahan Pammana Kabupaten Wajo - Andi Jamaluddin; Kori Hartono; Trisna Safitra; Reska Agusnawati (YP-SDI Lamaddukelleng, 2024)
Community service is one form of implementation of the Tri Dharma of Higher Education which includes education, research, and community service. This article examines the application of digitalisation of financial records through the E-Nota application for Micro, Small and Medium Enterprises (MSMEs) in Pammana Village. MSMEs often face problems in financial recording that is still done manually, which risks causing errors and losses. The E-Nota application comes as a solution to simplify the financial recording process digitally, so that MSMEs can manage their finances more effectively and efficiently. The results of the mentoring show that the use of E-Nota increases MSME actors' understanding of the importance of accounting in managing their business, and helps in making more accurate financial reports. With the application of this technology, it is hoped that MSMEs can survive and thrive in the digital era.